Community in Post-earthquake Writing from Haiti. Issue 2 (July 2014) - Munro, Martin
<x xml:space="preserve">Abstract</x> This article develops Celia Britton's insights into community in French Caribbean writing in two ways. First, it considers Jacques Roumain's Gouverneurs de la rosée and its image of community in the broader context of modern and contemporary Haitian fiction; and second it discusses representations of community in two Haitian works written after the earthquake of 2010, an event that literally destroyed many communities and has forced Haitian authors to rethink relationships between different groups in Haiti and between human life, the cities, nature and the land.